Obstacles to Exporting Micro,Small and Medium -Sized Enterprises - Cate Kyakuwa (Uganda Christian University, 2023)
The role of Micro, Small, and Medium Enterprises in shaping the economic landscape of Uganda cannot be overstated. These businesses serve as vital engines of growth, employment generation, and poverty reduction within the nation. The purpose of this paper was to discuss obstacles to Exporting by Micro, Small, and Medium Enterprises in Uganda. It seeks to unravel the factors that hinder these enterprises from realizing positive outcomes through their export, thereby impeding their goal of expanding sales. The research was guided by three objectives which are: (i) to identify the existing export policies and regulations of MSMEs in Uganda. (ii) to identify financial barriers faced by MSMEs in accessing capital for export activities in Uganda. (iii) to examine the training opportunities for MSMEs to enhance their export capacities in Uganda. The study utilized the content analysis research design, utilizing a qualitative research approach. The study focused on micro, small, and medium enterprises in Uganda. The Data utilized was drawn from secondary data sources which included various documents, on objective one, the study findings revealed that the existing export policies and regulations in Uganda provide a structured framework for international trade, ensure compliance with quality standards, mitigate risks, offer access to incentives, and open the door to global markets for MSMEs. On objective two, the study findings revealed that financial barriers for MSMEs seeking capital for export activities in Uganda have far-reaching implications for economic development, job creation, poverty reduction, and the country’s global competitiveness. On objective three, the study findings revealed that training opportunities, enhance long-term sustainability, global competitiveness, export compliance, collaboration, and networking, which fosters economic growth. I would recommend the government simplify export procedures, provide targeted financial support, expand export training, promote collaboration among MSMEs, offer market information access, facilitate advocacy, and establish effective monitoring mechanisms to help MSMEs overcome export obstacles and thrive in international trade. Keywords: Micro, Small, and Medium Enterprises (MSMEs)
This is a dissertation.